2022
DOI: 10.1116/6.0002055
|View full text |Cite
|
Sign up to set email alerts
|

On the chemistry mechanism for low-pressure chlorine process plasmas

Abstract: A chemical reaction mechanism of chlorine plasma under low-pressure conditions that is widely used in the literature is validated against the experimental data of Y. Wang and J. K. Olthoff [J. Appl. Phys. 85, 6358 (1999)] for an inductively coupled plasma reactor. The model used in the present study is a self-consistent two-dimensional fluid plasma model coupled with Maxwell’s equations. The quantities of interest in the plasma are the fluxes and energy distribution functions of Cl2+ and Cl+ ions. We find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Furthermore, the EAE is mainly investigated in electropositive or weakly electronegative CCPs, such as Ar, H 2 , H 2 /SiH 4 and O 2 discharges [35,[41][42][43][44][45][46][47][48], and the studies in strongly electronegative gases, such as Cl 2 , are rarely reported. Actually, high-density Cl 2 plasmas have been widely used in the etching process as a preferable reactant with semiconductors, metals and composite ferroelectrics films [14,[49][50][51] Therefore, the purpose of this paper is to employ a hybrid model, i.e. a global model coupled bi-directionally with an ion Monte-Carlo collision (MCC) sheath model, to investigate the EAE on the separate control of the ion flux and ion energy in Cl 2 ICPs with DF bias sources.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the EAE is mainly investigated in electropositive or weakly electronegative CCPs, such as Ar, H 2 , H 2 /SiH 4 and O 2 discharges [35,[41][42][43][44][45][46][47][48], and the studies in strongly electronegative gases, such as Cl 2 , are rarely reported. Actually, high-density Cl 2 plasmas have been widely used in the etching process as a preferable reactant with semiconductors, metals and composite ferroelectrics films [14,[49][50][51] Therefore, the purpose of this paper is to employ a hybrid model, i.e. a global model coupled bi-directionally with an ion Monte-Carlo collision (MCC) sheath model, to investigate the EAE on the separate control of the ion flux and ion energy in Cl 2 ICPs with DF bias sources.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of [10], Thorsteinsson and Gudmundsson [11] proposed convenient fitting formula which can be used for modeling of chlorine plasmas. Today, this fitting formula is used widely in both global and multidimensional plasma models to estimate the gas temperature [12,13].…”
Section: Introductionmentioning
confidence: 99%